Sons of Hellenism, Fathers of the Church Emperor Julian, Gregory of Nazianzus, and the Vision of Rome. - Elm, Susanna (Berkeley : University of California Press, 2012)
This groundbreaking study brings into dialogue for the first time the writings of Julian, the last non-Christian Roman Emperor, and his most outspoken critic, Bishop Gregory of Nazianzus, a central figure of Christianity. Susanna Elm compares these two men not to draw out the obvious contrast between the Church and the Emperor's neo-Paganism, but rather to find their common intellectual and social grounding. Her insightful analysis, supplemented by her magisterial command of sources, demonstrates the ways in which both men were part of the same dialectical whole. Elm recasts both Julian and Gr.
Oration 6, On Peace: Unity and Concord10. Gregory's Second Strike, Oration 5; The Pagan Context; Gregory's Second Strike against the Pagans; Procopius versus Valens; Conclusion: Visions of Rome; Governing the Oikoumene; Authority and Kinship of the Elites; Competing Universalisms; Bibliography; Index; A; B; C; D; E; F; G; H; I; J; K; L; M; N; O; P; Q; R; S; T; U; V; W; X; Z.
Description based on print version record.
Keywords: Church and state -- Rome; Church history -- Primitive and early church, ca. 30-600.; Gregory, -- of Nazianzus, Saint; Julian, -- Emperor of Rome, -- 331-363.; Rome -- History -- Julian, 361-363.; Rome -- Religion; Gregory, -- of Nazianzus, Saint; Julian, -- Emperor of Rome, -- 331-363.; Church and state -- Rome; Church history -- Primitive and early church, ca. 30-600.; Rome -- History -- Julian, 361-363.; RELIGION / Christian Church / History; RELIGION / Christianity / History; Electronic books